(untitled) (Strathmore Law Journal, 2023)
The doctrine of adverse possession conjures up deep emotional and philosophical arguments, centuries after its inception. While courts have perpetually been called upon to pronounce themselves on the fairness of the doctrine, a new formidable challenge has now been levelled against the principle-that of its relevance to 21st century land law. The debate rages on in courtrooms and parliamentary floors around the world, calling lawmakers, members of the bar and the bench to contribute to the keep or discard dichotomy. This paper makes an argument for the incompatibility of adverse possession with an era characterized by rigorous registration systems. The analysis begins by tracing the history of adverse possession and then proceeds towards an empirical assessment of the arguments in favour of, and against the doctrine. The discourse then contextualizes the discussion to Kenya’s land law and concludes by making an argument against the retention of the doctrine with respect to registered land.